SPECIFIC PERTUSSIS PREVENTION: PROBLEMS AND PERSPECTIVES - S.M. Kharit; O.L. Voronina; E.A. Lakotkina; T.V. Chernyaeva ("Paediatrician" Publishers LLC, 2007)
The lecture shows the modern state of the pertussis issue among the children. Based on the analysis of the presented data, the authors conclude that vaccination with the full cellular vaccine is rather safe; moreover, it protects the infants from the severe forms of the disease and lethal outcomes. However, the fact that there are children with constant contraindications to immunization with the full cellular vaccine, the change of the circulating B. pertussis serotypes, morbidity of the older children due to the loss of the postcvaccinal immunity define the necessity to introduce revaccination, as well as they are indications to the wider implementation of the non-cellular pertussis vaccine.Key words: pertussis, children, vaccination, full cellular pertussis vaccine, non-cellular pertussis vaccine.